1991
DOI: 10.1128/jvi.65.8.4525-4528.1991
|View full text |Cite
|
Sign up to set email alerts
|

The indirect association of human T-cell leukemia virus tax protein with DNA results in transcriptional activation

Abstract: trans-activator p40 of human T-cell leukemia virus type I activates specific enhancers and stimulates transcription of the viral and some cellular genes but does not bind directly to the enhancer sequences. We demonstrated here that a fusion protein of p4Ot^l and GAL4 DNA binding domain activated transcription dependent on the GAL4-binding site in the reporter plasmid. Mutants of p40 were also tested in the fusion protein, and their activities were found to be in parallel with those of their free forms on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 34 publications
(31 reference statements)
5
41
0
1
Order By: Relevance
“…The deletion findings are in agreement with those of others (10,13), who have shown that deletions in Tax were generally inactivating for function. This class of mutations represents changes that either were structurally disruptive or affected a common domain necessary for activating both LTRs.…”
Section: Resultssupporting
confidence: 92%
“…The deletion findings are in agreement with those of others (10,13), who have shown that deletions in Tax were generally inactivating for function. This class of mutations represents changes that either were structurally disruptive or affected a common domain necessary for activating both LTRs.…”
Section: Resultssupporting
confidence: 92%
“…According to several recent reports, Tax could stimulate viral transcription through enhancement of the DNA binding of CREB and ATF-2 to the 21-bp repeat (2,3,5,21,50,61,68,73,81). Others studies suggest that Tax could act through direct anchoring to the promoter via protein-protein interactions with the bound ATF/CREB proteins (14,22,23,71). Finally, Brauweiler et al (11) have recently provided evidence that Tax could stabilize the binding of CREB (but not ATF-2) to the 21-bp repeats.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA fragment encompassing the NR domain (1-493) was amplified by PCR and inserted into the pGal-BL (Fujisawa et al 1991) to obtain the effector expression vector pGal-NR. The reporter pG4-TK-Luc was constructed by inserting 4 copies of Gal4 binding sequence (gift of J. Fujisawa) into pTK-Luc which carries the promoter region of HSV-thymidine kinase gene (-197 -þ56).…”
Section: Measurement Of the Intrinsic Repression Activity Of The Nr Dmentioning
confidence: 99%